2018
DOI: 10.1200/jco.2017.76.6691
|View full text |Cite
|
Sign up to set email alerts
|

Sirolimus for Secondary Prevention of Skin Cancer in Kidney Transplant Recipients: 5-Year Results

Abstract: Purpose Transplant recipients who develop cutaneous squamous cell carcinomas are at high risk for multiple subsequent skin cancers. Sirolimus has been shown to reduce the occurrence of secondary skin cancers, but no study included a follow-up exceeding 2 years. We extended at 5 years the TUMORAPA randomized trial of sirolimus-based immunosuppressive regimen versus calcineurin inhibitor-based immunosuppression. Methods Kidney transplant recipients receiving calcineurin inhibitors who had at least one cutaneous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
1
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(80 citation statements)
references
References 37 publications
2
72
1
5
Order By: Relevance
“…Preliminary data suggest that conversion from calcineurin inhibitors to sirolimus reduces the incidence of skin cancer in renal graft recipients [95,97], possibly because sirolimus reduces vascularization and the thickness of post-transplant CSCCs [149]. The change of therapy from calcineurin inhibitors to sirolimus in patients with one CSCC lowered the risk of a new CSCC, and metastasis events only occurred in patients who received calcineurin inhibitors [96], the effect being maintained over five years of follow-up [150]. In vivo studies of hairless mice show that sirolimus significantly increases the latency of large tumors and reduces their multiplicity.…”
Section: Cyclosporine and Csccmentioning
confidence: 99%
“…Preliminary data suggest that conversion from calcineurin inhibitors to sirolimus reduces the incidence of skin cancer in renal graft recipients [95,97], possibly because sirolimus reduces vascularization and the thickness of post-transplant CSCCs [149]. The change of therapy from calcineurin inhibitors to sirolimus in patients with one CSCC lowered the risk of a new CSCC, and metastasis events only occurred in patients who received calcineurin inhibitors [96], the effect being maintained over five years of follow-up [150]. In vivo studies of hairless mice show that sirolimus significantly increases the latency of large tumors and reduces their multiplicity.…”
Section: Cyclosporine and Csccmentioning
confidence: 99%
“…And finally, everolimus is a hydroxyethyl ether derivative that is administrated to patients via oral (199). In addition, the prototype rapamycin (sirolimus) is also being tested in kidney transplant recipients, for preventing the occurrence of secondary skin cancers, which are common in these patients (200).…”
Section: Mtorc1 As a Therapeutic Targetmentioning
confidence: 99%
“…This finding was driven by increased cardiovascular deaths and infection‐related deaths and was found to be true in both patients taking sirolimus as first‐line therapy as well as after switching from a calcineurin‐based therapy. In contrast, results from the TUMORAPA randomized study by Dantal et al reported 5‐year follow‐up findings, which did not show differences in death rates. In a randomized study by Euvrard and colleagues in renal transplant recipients, 23% of the sirolimus group had to discontinue treatment because of the adverse effects, including edema, acneiform eruption, aphthous ulcers, and proteinuria.…”
Section: Discussionmentioning
confidence: 84%
“…Sirolimus and everolimus are mTOR inhibitors which have been used as immunosuppressants in transplant recipients. There is some long‐term randomized evidence and meta‐analyses which have demonstrated that sirolimus is associated with reduced NMSC incidence in renal transplant recipients, either as first‐line therapy or when switched from calcineurin inhibitors due to primary NMSC post transplant. On this note, it must be recognized that the risk of malignancies in solid organ transplantation is related to the level of immunosuppression, which is lower for kidney transplants compared to heart and lung organ transplantation .…”
Section: Introductionmentioning
confidence: 99%